Fravær som et kompositionsprincip i Helle Helles novellesamling 'Rester' (1996) - Cymbrykiewicz, Joanna (Wydawnictwo Naukowe UAM, 2009)
Artiklens formål er at foretage en analyse af Helle Helles novellesamling 'Rester' (1996), som er en af de mest opsigtvækkende novellesamlinger i 1990’ernes Danmark. Hovedvægten lægges på fravær, mangel og tab som samlingens dominerende kompositionsprincipper. Fraværsprincippet gælder for alle niveauer i teksten, dvs. for kompositionen, indholdet og sproget. Talrige eksempler på mangel- og tabstematikken bruges i artiklen for at anskueliggøre princippets relevans.

The paper analyses the short story collection titled 'Rester' (Remnants) written by the notable Danish author, Helle Helle. This work is characteristic of the contemporary minimalist movement, and is one of the most significant works of the 1990’s in Danish literature. The main point of the paper is the notion of absence and loss, which is treated as the work’s dominating principle. The paper attempts to prove that this governing principle of “absence and loss” both applies to the collection’s plot and its composition. Accordingly, several examples from the text are included to demonstrate the principle’s relevance.
The notion of absence as a structural principle in Helle Helle’s short story collection 'Rester' (1996)
Keywords: Helle Helle; novellesamling; fravær; kompositionsprincip; minimalisme; short story collection; absence; structural principle; minimalism